Students’ Response of Using Cornell Note Taking System (CNTS) in Listening Class - Syafii, Ahmad (English Education Department STKIP Al Hikmah Surabaya, 2019)
The main concern of the present study is to investigate the students’ response in CNTS in Literal Listening. This study employs descriptive qualitative method. It involves 18 students who enrolled in Literal Listening Class. Data was gathered through questionnaire and interview. The results of the study showed that note taking was still presumably considered as difficult skill because most lecturers were still not familiar to it. Consequently the students often struggle to decide what to note as the lecturers do not tell what to include in note. However, Cornel Note Taking System was generally proven helpful study tool in listening activity particularly it is because CNTS was a systematic guided note that perceived to be very helpful for students to be a good note taker. Suggestions are proposed for teacher particularly to prepare students with techniques of what to note and instroduce it earlier so that it would become the students’ habit. The results of this study may also be addressed for those who are interested in this field particularly English lecturers or lecturers who have problems in teaching listening.